Efficiency and dependence in the European electricity transition. (July 2021) - Percebois, Jacques; Pommeret, Stanislas
Abstract: Although the European Union sets common objectives, each member country is in charge of its own energy policy. An exhaustive analysis of the power generation mixes of the EU member countries from 1990 to 2017 has revealed strong disparities in the evolution of their structure. Using key performance indicators, the paper analyzes the current situation in terms of carbon intensity, dependence, vulnerability and energy transition dynamics. The paper focuses on the transition dynamics for 12 emblematic EU countries. It is worthwhile to note that most of these countries have managed to reduce the carbon intensity of their electricity. The analysis revealed, for some countries, an empirical relationship between imports and the carbon intensity of power generation. The increase of the share of renewable energies induces a dependence of a country on its neighbors as long as a massive storage of electricity is not available. The increased electricity trade with neighboring countries induce costs and benefits. Only countries that have invested heavily in hydro and nuclear power benefit from both a low-carbon electrical production mix and a low dependence on imports. Finally, the paper suggests some avenues for public policies in the energy field. Highligtjhs: The carbon intensity of the European electricity has been reduced during the last three decades. Electricity interconnections increased due to an increase of the intermittent production of renewables. Adding renewable to carbonaceous electricity is not enough to decarbonize the electricity. Large disparities remain among the European electrical production mixes.